2010
DOI: 10.1002/pssb.200983190
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the band‐gap of MgS and MgS‐rich Zn1−xMgxSySe1−y alloys from optical transmission measurements

Abstract: 451 3136As part of our development of an epitaxial lift-off process, utilising a sacrificial magnesium sulphide (MgS) layer, we have developed a MgS-rich ZnMgSSe alloy which provides excellent carrier confinement and resists both oxidation and acid attack. Here the optical transmission of the alloy has been measured and its bandgap determined as a direct transition at 4.19 AE 0.04 eV. Its composition has also been determined by X-ray interference (XRI) and comparison with simulations. For a range of alloy samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
(18 reference statements)
1
10
0
Order By: Relevance
“…The values predicted with TD-B3LYP display a slightly different trend however; D o is predicted by TD-B3LYP to first increase when going from MgS to MgO and then decreases again to MgSe. [35][36][37] The CdO D o is predicted by both TD-BHLYP and TD-B3LYP to be the smallest and thus most red-shifted of the (MO) 32 oxide series, as well as of all the (MX) 32 particles considered, while the 1.53 eV difference in the predicted D o between TD-BHLYP and TD-B3LYP is similar to that in the case of (MgO) 32 . Different from (MO) 32 , the lowest t 2 excitation is not always the lowest vertical excitation of the (MgX) 32 particles.…”
Section: Optical Gapmentioning
confidence: 64%
“…The values predicted with TD-B3LYP display a slightly different trend however; D o is predicted by TD-B3LYP to first increase when going from MgS to MgO and then decreases again to MgSe. [35][36][37] The CdO D o is predicted by both TD-BHLYP and TD-B3LYP to be the smallest and thus most red-shifted of the (MO) 32 oxide series, as well as of all the (MX) 32 particles considered, while the 1.53 eV difference in the predicted D o between TD-BHLYP and TD-B3LYP is similar to that in the case of (MgO) 32 . Different from (MO) 32 , the lowest t 2 excitation is not always the lowest vertical excitation of the (MgX) 32 particles.…”
Section: Optical Gapmentioning
confidence: 64%
“…None of the samples received an additional ZnSe capping layer, as the ZnMgSSe alloy has been found to resist oxidation sufficiently, to protect them [3].…”
Section: Growthmentioning
confidence: 99%
“…MgS is an excellent barrier material with a bandgap of $ 4.8 eV and we have previously shown that it can be used as a barrier for both ZnSe quantum wells and CdSe dots [3,4]. It cannot however be used as such in structures where lift-off is also required.…”
Section: Introductionmentioning
confidence: 98%
“…The use of a semiconductor layer which can be preferentially etched away was first demonstrated by Konagai et al 1 and then later further developed by Yablonovitch et al for structures lattice matched to GaAs using an AlAs sacrificial layer 2. We have subsequently demonstrated that MgS can successfully be used as a sacrificial layer in the epitaxial lift‐off (ELO) of II–VI heterostructures grown lattice matched to GaAs 3, 4. To date, we have shown that after lift‐off epitaxial structures can be transferred either to glass, fused silica, or lithium niobate 3–6 and we believe that this could be further extended to almost any substrate material so long as it is chemically compatible with the material being deposited.…”
Section: Introductionmentioning
confidence: 99%
“…We have subsequently demonstrated that MgS can successfully be used as a sacrificial layer in the epitaxial lift‐off (ELO) of II–VI heterostructures grown lattice matched to GaAs 3, 4. To date, we have shown that after lift‐off epitaxial structures can be transferred either to glass, fused silica, or lithium niobate 3–6 and we believe that this could be further extended to almost any substrate material so long as it is chemically compatible with the material being deposited. Additionally, we have also shown that it is possible to construct high Q micro‐cavities by depositing material directly onto dielectric mirrors 7, 8.…”
Section: Introductionmentioning
confidence: 99%